Double‐blind randomized controlled trial of collagen mesh for the prevention of abdominal incisional hernia in patients having a vertical rectus abdominis myocutaneus flap during surgery for advanced pelvic malignancy. (May 2017) - Mortensen, A. R.; Grossmann, I.; Rosenkilde, M.; Wara, P.; Laurberg, S.; Christensen, P.
Abstract: Aim: The study investigated the effect of collagen mesh‐assisted closure at the donor site in preventing the formation of incisional hernia following construction of a vertical rectus abdominis myocutaneus (VRAM) flap as part of pelvic surgery for recurrent colorectal cancer. Method: The study was a double‐blinded randomized controlled superiority trial that was designed and performed according to the Consolidated Standards of Reporting Trials (CONSORT) Statement. Eligible patients undergoing surgery that included a VRAM flap for advanced colorectal pelvic malignancy were prospectively randomized to conventional abdominal wound closure or collagen mesh‐assisted closure. The primary end‐point was incisional herniation at 1 year confirmed by CT. Secondary end‐points were CT‐verified incisional herniation at 3 and 36 months, clinically recognizable incisional herniation, donor‐site and reconstructive‐site complications, surgical mortality, postoperative morbidity, postoperative recovery and survival. Results: In total, 58 (29 conventional closure; 29 mesh‐assisted closure) patients were included. At 1 year, incisional herniation on the CT scan was found in 12 (50%) of 24 patients in the conventional closure group, and in 8 (33%) of 24 in the mesh‐assisted closure group ( P = 0.38). No significant difference between the groups was found in surgical mortality, early or late complications or survival. Donor‐site morbidity was comparable between the two groups. Conclusion: No preventative effect of collagen mesh‐assisted closure was observed following VRAM flap reconstruction.